Research on pricing zone division strategy based on natural gas tariff affordability - Nini YU; Yuanyuan ZHANG; Jinyue LI; Yao WANG; Yanwen LIN; Simin CHEN (You-qi chuyun)
Objective The existing method of dividing natural gas pricing into four zones in China overlooks variations in tariff affordability among provinces (municipalities) within these price zones, thereby highlighting a lack of uniformity and objectivity. To optimize this pricing zone division, it is imperative to explore a pricing zone division strategy from the perspective of tariff affordability across the 31 provinces (municipalities) in China's mainland. Methods An evaluation index system was initially constructed based on five aspects: economy, society, energy, environment, and the natural gas industry. Additionally, an entropy-weighted Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) model was established, which was used to derive the scores of first-level indexes affecting tariff affordability across all the provinces (municipalities), as well as the total scores of tariff affordability. Furthermore, the between-group linkage method was chosen to cluster both the scores of first-level indexes and the total scores of tariff affordability. The number of clusters was determined using the elbow method. Results Based on the clustering results, Shandong and the Tibet Autonomous Region corresponded to the highest and lowest levels of tariff affordability, respectively, supporting their classification into separate zones. A significant difference in tariff affordability was revealed between coastal provinces and inland provinces within the pricing zone of central and eastern China. Specifically, tariff affordability in coastal provinces (municipalities) such as Guangdong, Jiangsu, and Zhejiang is relatively high, whereas it is comparatively low in inland provinces (municipalities) like Beijing, Tianjin, and Hebei, where the clustering results were also stable. Additionally, Liaoning, with a noticeable tariff affordability distinction compared to the rest of the northeastern China pricing zone, particularly Heilongjiang and Jilin, aligned more closely with the coastal provinces (municipalities) in central and eastern China. Other provinces (municipalities) in central China showed relatively concentrated evaluation scores and small intra-cluster distances. Conclusion It is proposed to divide China into six natural gas pricing zones. The existing central and eastern China pricing zone is further divided into an inland pricing zone and a coastal pricing zone, and the latter includes Liaoning. Shandong and the Tibet Autonomous Region are designated as two special pricing zones. The remaining provinces (municipalities) in central China, with small differences in tariff affordability scores, are classified into a single zone. This proposed method results in closer tariff affordability within each pricing zone, thereby facilitating the transformation of the approach to dividing natural gas pricing zones.